Potentially modifiable patient factors in mandible fracture complications: a systematic review and meta-analysis. Issue 1 (January 2022) - Ahmed, Asad; Wu, Eiling; Sarai, Rupinder; Williams, Rhodri; Breeze, John
Abstract : Introduction: The mandible is the most common bone to develop complications following treatment of facial fractures. This is due to a complex interaction of both fracture specific and patient factors. Our aim was to identify those patient factors, with a specific focus on those that may be potentially modifiable to reduce the incidence of complications. Methods: A systematic review of the literature was undertaken using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses methodology to identify patient factors ascribed to an increased risk of complications following mandible fracture treatment. These were divided non- modifiable and potentially modifiable factors. A meta-analysis was performed to weight those factors for which statistical analysis had been performed. Results: 22 pertinent papers were identified, of which 8 described non-modifiable and 7 potentially modifiable factors. The most common potentially modifiable factor identified was smoking. Meta-analysis established that tobacco smoking demonstrated an increased risk of complications in three studies (OR: 4.04 – 8.09). Conclusions: Division of patient factors into those that are potentially modifiable and those that are not will enable clinicians to focus on those in which change within the immediate post-operative period can be instigated. This includes smoking cessation assistance, education as to the need for a soft diet and facilitating post- operative clinic attendance. It also enables stratification of risk in terms of consent, and choice of treatment. Further research should use standardised terminology, particularly in stopping the use of generalizable terms such as patient compliance and instead describing its individual components.